Investigating Pesticide Residue in Some Vegetables Grown in Paksong District of Champasak Provinces of Lao PDR - Vansavang, Viengkhong; Saiyalard, Sengchan; Kongmany, Santi; Soukchalern, Phoungkeo; Phomsupha, Souksamlarn (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study aimed to investigate the pesticide residues of 6 pesticide active compounds (Methyl-chlorpyrifos, Chlorpyrifos, Malathion, beta-Cyhalothrin, lamda-Cyhalothrin and Cypermethrin) in 3 kinds of vegetables (Cabbage, Chinese cabbage and chili) in the farms of six villages (Thongkalong/TKL, Thongset/TS, Nongsoung/ NS, KaToud/KT, NonChan/NC and Khongtoon/KHT) in Paksong district of Champasak province of the Lao PDR. The samples were collected in March of 2022, and they were analyzed by using the QuEChERS method and detected by Gas Chromatograph Electron Capture Detector calibrated with the targeted pesticide standards. The results showed that Malathion residues were found in Cabbage (0.213 mg/kg) and Chinese cabbage (0.185 mg/kg) samples from KT. Malathion residue of 0.300 mg/kg was found in chili sample from TS. Furthermore, Malathion residues were found in Cabbage (0.458 mg/kg) and Chinese cabbage (0.201 mg/kg) samples from TKL. Chlorpyrifos residue of 0.135 mg/kg was found in KT cabbage sample. The Malathion, Chlopyrifos and Beta-cyhalothrin residues of 0.292, 0.143 and 2.338 mg/kg, respectively, were found in NC chili sample. In summary, it was indicated that there were the target pesticide residues in all vegetable samples at the levels above MRL defined by Codex/WHO. For consumer’s safety, the vegetable harvesting period must be in general spaced for 10-15 days after pesticide application. However, the results of this study would be a good and important information for concerning sectors in terms of research and risk assessment for food safety in Laos in the future.